Optimization of Dynamic Packet Length in Wireless Sensor Network (International Journal of Engineering and Computer Science, 2014)
In wireless sensor network, packet size optimization is an important issue in energy constrained. We provide dynamic packet length optimization scheme to achieve best performance in terms of channel utilization, energy efficiency. The adaptation of dynamic packet length is 802.11 wireless system. We increase data delivery ratio, system throughput and decrease network conjunction, end to end delay. In the system, the packet delivery ratio keeps high i.e. 95% above and link estimated error within 10% for 95% link. The system provides accurate link estimation method which achieves best performances related to the previous works.